PENGGUNAAN INTERNET DAN MEDIA SOSIAL ORANG MUDA DI PEDESAAN (Studi Kasus Orang Muda di Desa Ciasmara Kecamatan Pamijahan Kabupaten Bogor) - Jayawinangun, Roni; Nugra, Yogaprasta Adi (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
Abstract Digital developments show a positive trend from year to year, especially for Indonesia based on data from WeAreSocial that collaborates with Hootsuite in 2018, it is known that the number of internet users reaches 132 million people. This number shows that half or more than 50 percent of Indonesia's population can access the internet. Young people and the internet are two things that are closely related. The magnitude of the penetration of young people relates to the type of content accessed. Based on this, it is interesting to know the use of internet and social media for young people in rural areas. This study aims to: 1) Know the internet use of young people in Ciasmara Village; 2) Knowing the use of social media for young people in Ciasmara Village. Quantitative methods are used to process data using descriptive analysis to determine the characteristics of respondents and the use of the internet and social media. This study found that the internet use of young people in Ciasmara Village is known that the largest frequency is rare, with an average duration of 3.4 hours per week, access on social media, the place / media used is mobile phones. The use of social media for young people in Desa Ciasmara is known that the biggest frequency is rare, with an average duration of 2.6 hours per week access to social media, the place / media used is school computers. Keywords: Young people, rural, internet use, social media use.